Hubungan Antara Kecerdasan Spiritual sengan Stres Kerja pada Perawat RS di Klaten - Ridwan Umamit; Siti Mulyani (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2016)
This study was aimed to examine the correlation of spritual intteligence and job stress in nurse. This hypothesis posed in this study were there is a negative correlation between spiritual intelligence and job stress. The subject of this study were nurse of emergency and inpatient unit at the hospital in Klaten, totaling 101 people. Data were collected by using spiritual intelligence and job stress scale. The data is was then statistically analyzed using Pearson product moment analysis with SPSS SPSS version 15.0 for windows. The analysis found correlation coefficient of (r-xy) = -0.315, p = 0.001 (p <0.01), the determinant coefficient r2 = 0.099, indicates that the effective contribution of spiritual intelligence to job stress by 9.9%. Base on the analyse can be concluded that there was a significant negative correlation between spiritual intelligence with work stress on nurses. These results illustrate that the higher spiritual intelligence, the lower the stress of work. Conversely the lower the higher spiritual intelligence stress of work or hypothesis is acceptedÂ Keywords: Spritual Intteligence, Job stress, Nurse